2016
DOI: 10.1103/physrevlett.117.182502
|View full text |Cite|
|
Sign up to set email alerts
|

Prediction for a Four-Neutron Resonance

Abstract: We utilize various ab initio approaches to search for a low-lying resonance in the four-neutron (4n) system using the JISP16 realistic NN interaction. Our most accurate prediction is obtained using a J-matrix extension of the no-core shell model and suggests a 4n resonant state at an energy near E_{r}=0.8  MeV with a width of approximately Γ=1.4  MeV.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(44 citation statements)
references
References 35 publications
5
39
0
Order By: Relevance
“…Consequently, we suppose that trineu-tron should be more likely to be observed experimentally than tetraneutron. We also compared our calculations The corresponding references are QMC: [14], NCSM2016: [13] and NCSM2018: [20]. The experimental datum is from Ref.…”
Section: Calculations and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, we suppose that trineu-tron should be more likely to be observed experimentally than tetraneutron. We also compared our calculations The corresponding references are QMC: [14], NCSM2016: [13] and NCSM2018: [20]. The experimental datum is from Ref.…”
Section: Calculations and Discussionmentioning
confidence: 99%
“…The widths of the eigenstates obtained in NCGSM take all particleemission channels into account, so that they are total decay widths. Conversely, other methods, as those using Faddeev-Yakubovsky equations [17] and NCSM calculations [13], need to consider all partial decay processes to calculate the total decay width.…”
Section: The Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering possible systematic uncertainties in the E906 data and in the SMM calculations, even for B( 4 ΛΛ n) = 1 MeV the signal strength of N 2 /N total = 0.16 is still compatible with the data. As mentioned before, the initial excitation energy of the 10 ΛΛ Li * depends on the binding energy of the Ξ − at the time 7 of conversion. We, therefore, repeated the SMM calculations for an excitation energy of 25 MeV.…”
Section: Can a Neutralmentioning
confidence: 79%
“…In case of the stopped Ξ − process a capture × conversion probability for producing excited ΛΛ nuclear systems of 5% was taken into account. The probabilities in the last 5 columns are multiplied by 10 6 Λ He would contribute at p π−L ≈ 108 MeV/c. In early emulsion studies, however, no two-body decays of 6 Λ He were found, although the decays of the neighboring isotopes 5 Λ He and 7 Λ He have been seen [42], indicating the potential sensitivity of these experiments to 6 Λ He → 6 Li+π − decays.…”
Section: The E906 Puzzlementioning
confidence: 99%